Antimicrobial resistance genes and associated mobile genetic elements in Lactobacillales from various sources - Kaszab, Eszter; Laczkó, Levente; Kardos, Gábor; Bányai, Krisztián (Frontiers in Microbiology, 2023)
Lactobacillales are commonly used in food products and as probiotics in animal and human medicine. Despite being generally recognized as safe, lactic acid bacteria may harbor a variety of antimicrobial resistance genes (ARGs), which may be transferable to human or veterinary pathogens, thus, may pose veterinary and public health concerns. This study investigates the resistome of Lactobacillales. A total of 4,286 whole-genome sequences were retrieved from NCBI RefSeq database. We screened ARGs in whole genome sequences and assessed if they are transmissible by plasmid transfer or by linkage to integrative mobile genetic elements. In the database, 335 strains were found to carry at least one ARG, and 194 strains carried at least one potentially transferable ARG. The most prevalent transferable ARG were tetM and tetW conferring antibiotic resistance to tetracycline. This study highlights the importance of the One Health concept by demonstrating the potential for Lactobacillales, commonly used in food products, to serve as reservoirs and vectors for ARGs.